Environmental impact of feeding plant-based vs. meat-based dry dog foods in the United Kingdom - Brociek, R. A.; Gardner, D. S. (Frontiers in Sustainable Food Systems, 2025)
IntroductionPet food production contributes substantially to global environmental pressures, driven largely by animal-derived ingredients. The current study quantified the environmental impacts of 31 commercially available dry dog foods purchased in the United Kingdom, categorised as plant-based, poultry-based, red meat-based (beef and lamb) and veterinary renal diets.MethodsEnvironmental metrics including land use (m2/1000 kcal), greenhouse gas emissions (kg CO₂eq/1000 kcal), acidifying emissions (g SO₂eq/1000 kcal), eutrophying emissions (g PO₄3−eq/1000 kcal), and freshwater withdrawal (L/1000 kcal) were estimated using life cycle assessment datasets and adjusted for ingredient composition, energy density and differences in moisture content.ResultsPlant-based diets had the lowest impact across all measures of environmental impact. Poultry-based and veterinary diets were intermediate, while beef- and lamb-based foods had substantially higher impact compared to all other foods. For example, per 1,000 kcal dry food, beef-based diets required an estimated 102.15 m2 land to produce (vs. 2.73 m2 for plant-based) and emitted an estimated 31.47 kg CO₂eq (vs. 2.82 kg for plant-based). Beef-based foods generated 7.1-fold higher acidifying emissions and 16.4 fold higher eutrophying emissions, compared to plant-based foods.ConclusionProduction of animal-based pet foods has significantly greater environmental impact, when compared to production of plant-based pet foods. Higher inclusion of plant-based ingredients in pet feed provides a major opportunity for pet food companies to mitigate the environmental footprint of companion animal food.